Kajian sedimentasi Sungai Larona pada daerah aliran Sungai Larona Kabupaten Luwu Timur - Syamsuddin, Syamsuddin; Musa, Ratna; Mallombassi, Ali (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Sediment produced by the erosion process and carried by water flow, will be deposited in a place where the flow rate slows down or stops. The occurrence of sedimentation can affect the morphological conditions of the river where the elevation of the river bed will decrease due to shallowing. As a result, the water capacity in the river is reduced so that it cannot maximize the function of the river. This study aims to determine the magnitude of the sediment transport rate and the volume of sediment transport in the Larona River in the Larona River Area in the Larona River located in Pongkeru Village, Malili District, East Luwu Regency, South Sulawesi Province. The results of this study indicate that the sediment rate of the Larona River was obtained at 23016.24 tons / ha / year and the volume of sediment transport in the Larona River in the Larona River Basin was obtained at 15.46 m3/year.